A systematic review of the 'eating disorder voice' experience. (19th May 2019) - Aya, Viviana; Ulusoy, Kubra; Cardi, Valentina
Abstract: The 'eating disorder voice' experience has been reported by both clinicians and by patients with eating disorders (ED) as an important feature of eating psychopathology, however this has only become an area of research in the last decade. The main aim of this paper was to systematically review and synthesize the available literature on this topic. Systematic searches of seven electronic databases were performed up to June 2018. Thirteen peer-reviewed articles were identified. Findings suggested that the existence of an 'ED voice' is often recognized by patients with eating disorders and that this voice has a powerful, negative and omnipotent nature. Feelings of entrapment and defeat are commonly experienced in response to it and patients appear ambivalent towards it. The negative characteristics and responses to the voice are associated with eating disorder symptoms. Addressing the eating disorder voice using relational and interpersonal approaches has the potential to improve clinical and treatment outcomes for patients with eating disorders.